Strategic Management Practices within the Romanian Hotel Industry - Ovidiu-Niculae Bordean; Anca Borza (Amfiteatru Economic)
The fierce competition among hotels had forced managers to reconsider the way in which they are doing business. The strategic planning is seen as one approach that could help hotel managers to bust their hotel performance and to obtain a competitive advantage against the other hotels. This paper addresses the issue of strategic management in the hotel industry through a survey designed to identify the strategic practices that hotels from the North-Western part of Romania are using. The research study was based on a questionnaire that was administered to 65 key decision makers from the hotel industry in five large cities. The aim of the study was to offer a real picture of the strategic approaches that are implemented within the hotel industry. The study uses 25 statements that largely correspond to some of the most-cited strategic practices within the strategic management tourism literature. The hotels that took part in the study focused mainly on implementing the differentiation and innovation strategy. The ANOVA test showed that there are significant differences between the way in which these strategies are pursued according to several characteristics of the hotels (size, category and management type). The results offer valuable and consistent insights for both hotel managers who wish to develop better strategies and theoreticians who are interested in filling in the existing gap from the hotel literature.